Perbedaan Leaflet dan Flashcard dalam Meningkatkan Pengetahuan Siswa tentang Bahaya Perokok Pasif - Ledya Yubilda Taneo; Christina R. Nayoan; Fransiskus G. Mado; Marni Marni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Secondhand smoke exposure remains a serious public health issue, particularly for children in elementary school environments. Educational interventions using appropriate media are essential to increase students’ knowledge and awareness of its dangers. This study aimed to compare the effectiveness of leaflet and flashcard media in improving students’ knowledge about the dangers of passive smoking at SDK St. Yoseph Noelbaki. A quasi-experimental method with a pretest-posttest two-group design was employed. The sample consisted of fourth- and fifth-grade students divided into two intervention groups, each receiving education using either leaflet or flashcard media. Knowledge levels were assessed using a structured questionnaire administered before and after the intervention. The findings revealed that both media significantly improved students’ knowledge (p < 0.05). However, the Mann-Whitney test showed no statistically significant difference between the two groups (p = 0.825), indicating that both media were equally effective. Descriptively, the flashcard group showed a slightly higher mean increase in knowledge scores than the leaflet group, though the difference was not statistically significant. These results suggest that both leaflet and flashcard media can serve as effective educational tools for enhancing elementary students’ understanding of the health risks associated with passive smoking.